Shared mechanisms in physiological and pathological nucleoplasmic reticulum formation. (2nd January 2017) - Drozdz, Marek Mateusz; Vaux, David John
ABSTRACT: The mammalian nuclear envelope (NE) can develop complex dynamic membrane-bounded invaginations in response to both physiological and pathological stimuli. Since the formation of these nucleoplasmic reticulum (NR) structures can occur during interphase, without mitotic NE breakdown and reassembly, some other mechanism must drive their development. Here we consider models for deformation of the interphase NE, together with the evidence for their potential roles in NR formation.